Fabrication of PLA/COW dung-based biocomposite - Yusefi, Mostafa (2015)
Various environmental drawbacks such as reduction in land fill space and nonbiodegradability lead to systematically investigate the replacing of synthetic composites by using biocomposites. Biocomposites possess suitable characterizations such as light weight, combustible, nontoxic, and biodegradability behavior. However, the final product of the biocomposites carries certain drawbacks in terms of mechanical, physical and thermal properties. In order to determine their characteristic, this research aided to figure out the possibility of applying cow dung (CD) as filler to prepare polylactic acid (PLA) biocomposite. The main objective of this research is to obtain a suitable composition ratio based on the filler and the hosting polymer. The CD of two different sizes, namely 4.00 mm and 0.5 mm were blended with PLA. PLA/CD biocomposites with different CD ratios (0-60 wt.%) were fabricated using an internal Brabender mixer (W50EHT-3zones) followed by a 40 tones hydraulic compression moulding. The results showed that the addition of CD led to improve flexural properties compared to tensile and impact strength. Biocomposites with 4.00 mm CD (bigger filler) mainly showed higher mechanical properties than those of 0.5 mm CD (smaller filler). Scanning electron microscopy (SEM) of tensile and impact fractured surfaces indicated that the bigger fillers had stronger adhesion and bonding with the matrix. Moreover, the cavities and rough surface of biocomposites increased with the filler content addition. This led to lower mechanical and physical properties of the biocomposites and increased water uptake during water absorption test accordingly. Dynamic mechanical analysis (DMA) technique was also followed to determine both storage and loss modulus of the samples. Neat PLA indicted the lowest storage modulus, while the filler content addition generally improved the storage modulus. Results of hermogravimetric analysis (TGA) indicated that the addition of the filler content prolonged the major degradation temperature. This was due to the higher resistance of the CD filler to the degradation temperature, which induced higher thermal stability of CD compared to the neat PLA.